A low-cost and highly integrated control system for lower limb rehabilitation robot. (2017) - Cao, Fucheng; Li, Yuanchun; Wang, Lirong; Liu, Zhen
This paper presents a lower limb rehabilitation control system designed to train stroke patients by providing variable damping on the knee joint. The hardware based on the controller TMS320F28335 digital signal processor (DSP) and the software based on the DSP/BIOS embedded operation system are designed. The effective control of brushless DC (BLDC) motor can be implemented by combining with the upper impedance control algorithms and the underlying field-oriented control (FOC) control algorithm, which improves the performance of rehabilitation robot control system. The proposed integrated control system has robustness, dependability and works in real-time, and is easy to be upgraded and expanded.